2018
DOI: 10.1371/journal.pone.0191228
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing in neurogenetic odysseys: An effective, cost- and time-saving diagnostic approach

Abstract: BackgroundDiagnostic trajectories for neurogenetic disorders frequently require the use of considerable time and resources, exposing patients and families to so-called “diagnostic odysseys”. Previous studies have provided strong evidence for increased diagnostic and clinical utility of whole-exome sequencing in medical genetics. However, specific reports assessing its utility in a setting such as ours- a neurogeneticist led academic group serving in a low-income country—are rare.ObjectivesTo assess the diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 29 publications
2
72
0
5
Order By: Relevance
“…A change of patient medication, either initiation of a new treatment or halting of an existing one, was specifically reported in 22 studies. 8,[15][16][17][18]20,22,23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39] For example, Anazi et al reported a patient with ID who was homozygous for a truncating pathogenic variant in SLC39A14 that causes a potentially treatable form of hypermanganesemia, who was started on chelation therapy, resulting in improved manganese levels. 17 In a case series of patients with presumed neurogenetic disorders and DD/ID from Argentina, 10% (4/ 40) underwent a trial of new medication following ES, including a trial of L-Dopa in a patient with paraplegia and ID who had pathogenic variants in SPG11 and a trial of acetazolamide and fampridine in a patient with a pathogenic variant in KCNA2.…”
Section: Medication and Dietary Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…A change of patient medication, either initiation of a new treatment or halting of an existing one, was specifically reported in 22 studies. 8,[15][16][17][18]20,22,23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39] For example, Anazi et al reported a patient with ID who was homozygous for a truncating pathogenic variant in SLC39A14 that causes a potentially treatable form of hypermanganesemia, who was started on chelation therapy, resulting in improved manganese levels. 17 In a case series of patients with presumed neurogenetic disorders and DD/ID from Argentina, 10% (4/ 40) underwent a trial of new medication following ES, including a trial of L-Dopa in a patient with paraplegia and ID who had pathogenic variants in SPG11 and a trial of acetazolamide and fampridine in a patient with a pathogenic variant in KCNA2.…”
Section: Medication and Dietary Managementmentioning
confidence: 99%
“…17 In a case series of patients with presumed neurogenetic disorders and DD/ID from Argentina, 10% (4/ 40) underwent a trial of new medication following ES, including a trial of L-Dopa in a patient with paraplegia and ID who had pathogenic variants in SPG11 and a trial of acetazolamide and fampridine in a patient with a pathogenic variant in KCNA2. 39 In the same study, physicians made recommendations to avoid statins in a patient with a pathogenic variant in DMD and to avoid drugs (unspecified) with mitochondrial toxicity in a patient with a MT-ATP6 pathogenic variant causing DD and epilepsy. 39 Alterations to a patient's existing diet were mentioned in nine studies.…”
Section: Medication and Dietary Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…WGS/WES has led to an increased diagnostic yield in patients with suspected rare genetic conditions and in some cases, molecular diagnosis results in better prognosis and recommendations for surveillance of disease-related complications (17,26,27). Although the financial implications associated with WGS/WES may be costly, utilizing this technology in patients with undiagnosed or suspected genetic diseases, who may otherwise go through lengthy, costly, and unfruitful diagnostic tests, may be expected to not only improve quality of patient care but also yield cost-saving returns in the long term, given the exceptionally high cost of these patients as is (28,29). Pediatric ACOs should be in position to drive the reimbursement policies of WGS/WES and the guidance on the best practice on the utilization of WGS/WES.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we would like to remark that several research/ clinical groups are using genomic approaches for the study and diagnosis of genetic disorders such as neurological disorders (Cordoba et al, 2018;Rodriguez-Quiroga et al, 2015), Duchenne/Becker muscular dystrophy (Luce et al, 2018), breast cancer (Solano et al, 2017, ovarian cancer (Cardoso et al, 2018), and endocrine/immune diseases (Gutierrez et al, 2018), among others.…”
mentioning
confidence: 99%